2002
DOI: 10.1038/nature00821
|View full text |Cite
|
Sign up to set email alerts
|

VEGF regulates haematopoietic stem cell survival by an internal autocrine loop mechanism

Abstract: Vascular endothelial growth factor (VEGF) is a principal regulator of blood vessel formation and haematopoiesis, but the mechanisms by which VEGF differentially regulates these processes have been elusive. Here we describe a regulatory loop by which VEGF controls survival of haematopoietic stem cells (HSCs). We observed a reduction in survival, colony formation and in vivo repopulation rates of HSCs after ablation of the VEGF gene in mice. Intracellularly acting small-molecule inhibitors of VEGF receptor (VEGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
452
3
14

Year Published

2003
2003
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 645 publications
(491 citation statements)
references
References 27 publications
22
452
3
14
Order By: Relevance
“…More recently, VEGF 165 has been demonstrated to promote survival in an autocrine manner for a number of other cell types, including podocytes [10], renal tubular epithelial cells [11], haematopoietic stem cells [12] and tumour cells [13].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, VEGF 165 has been demonstrated to promote survival in an autocrine manner for a number of other cell types, including podocytes [10], renal tubular epithelial cells [11], haematopoietic stem cells [12] and tumour cells [13].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, KDR promotes both cell growth and survival, thus implying that the growth increase may be caused by its antiapoptotic effect. 14,16,20 In the early phases of VEGF treatment in GM-CSF-supplemented cultures, we could uncouple the cell growth effect from the antiapoptotic action. In these conditions, KDR stimulation, while not exerting a survival effect, causes: (a) a slight, but significant increase of cell growth, and particularly (b) a sharp rise of mitotic figures.…”
Section: Discussionmentioning
confidence: 99%
“…19 In line with these findings, adult murine VEGF (À/À) cells show a sharp depletion of the HSC pool: importantly, treatment with VEGF mutants revealed that activation of KDR is sufficient to rescue the HSC activity. 20 Specifically, KDR favors self-renewal and survival of primitive hematopoietic cells. 8,20,21 The functional role of KDR at more advanced stages of hematopoiesis is under investigation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations